2007
DOI: 10.1158/1078-0432.ccr-07-0266
|View full text |Cite
|
Sign up to set email alerts
|

Different Prognostic Roles of Mutations in the Helical and Kinase Domains of the PIK3CA Gene in Breast Carcinomas

Abstract: Purpose: In breast cancer, the PIK3CA gene is frequently mutated at ''hotspots'' in exons 9 and 20, corresponding to the helical and kinase domains, respectively. We decided to investigate the association of PIK3CA mutations with pathologic features and clinical outcome in a large series of patients with breast cancer. Experimental Design: Frozen samples from 163 consecutive patients were analyzed for PIK3CA mutations using PCR single-strand conformation polymorphism and sequence analyses. Results: We identifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
171
5
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 184 publications
(197 citation statements)
references
References 21 publications
18
171
5
3
Order By: Relevance
“…[18][19][20][21][22][23] Prior studies have failed to identify PIK3CA mutations in histologically normal breast tissue, even with the same sensitive methods employed here. 1,8,16,19 In this study, we demonstrated a 50% frequency of PIK3CA point mutations in usual ductal hyperplasia and columnar cell lesions across 62 lesions, representing the largest series to date. We also found similarly a high frequency of PIK3CA mutations in smaller cohorts of atypical ductal lesions (71%) and lobular neoplasia (44%), and a near-lack of other 'hotspot' activating mutations in genes such as AKT1.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…[18][19][20][21][22][23] Prior studies have failed to identify PIK3CA mutations in histologically normal breast tissue, even with the same sensitive methods employed here. 1,8,16,19 In this study, we demonstrated a 50% frequency of PIK3CA point mutations in usual ductal hyperplasia and columnar cell lesions across 62 lesions, representing the largest series to date. We also found similarly a high frequency of PIK3CA mutations in smaller cohorts of atypical ductal lesions (71%) and lobular neoplasia (44%), and a near-lack of other 'hotspot' activating mutations in genes such as AKT1.…”
Section: Discussionmentioning
confidence: 58%
“…Activating PIK3CA point mutations are among the most common genetic aberrations in invasive breast cancer, [1][2][3][4][5][6][7][8][9][10] and several studies have shown that these mutations exist at nearly the same frequency in DCIS. [14][15][16][17] Accumulating evidence suggests that PIK3CA point mutations may also be common in other proliferative breast lesions such as benign papillomas and columnar cell lesions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations